REPRESENTASI DAMPAK NEGATIFMEDIA BARU DALAM FILM DON’T HUG ME I’M SCARED 4 - Dwino Setyo Moreaz; Suyanto " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Film is a medium of communication which contains a lot of messages and meanings. Film is not only serves merely for entertainment but also as a medium of messenger. One form of messages that can be conveyed through the film is a social critique. Don’t Hug Me I’m Scared 4 is one of those films that use the theme of social criticism which is about the use of new media. This study aims to determine the meaning of denotation, connotation, and the myth of the Don’t Hug Me I’m Scared 4 film which represents the negative impact of new media.This study’s method is qualitative research methods with semiotic approach of Roland Barthes which consist of denotation, connotation, and myth meaning. Data was collected through documentation technique. In accordance with Barthes semiotic theory, the data analysis techniques of this study conducted in accordance with Barthes semiotic analysis framework consisting of denotation, connotation, and also myth meaning. The unit of data analysis in this study consisted of three scenes that contained in the Don’t Hug Me I’m Scared 4 film.According to denotation meaning, the negative impact of new media that represented on Don’t Hug Me I’m Scared 4 are new media has degrade privacy value of user’s personal data, new media has a tendency to give information that is not accurate, new media as a self representation medium potentially drive the users to a spoil habit, new media potentially make users trapped in overuse of entertainment and also change or even dismiss the form of interaction and socialization in real life. According to connotation meaning, the negative impact of new media that represented are new media dismiss the privacy of user’s personal data, new media has a tendency to drive users to misinformation, new media potentially raise the narcissistic behavior, new media potentially give raise to addictive effect and also make users to be alienated from their real social space. According to myth meaning, the negative impact of new media that represented are new media create a new perspective that is value of user’s personal data is no longer considered as an important thing to keep, new media cause information exceed its function limit, New media uses has a tendency to raise boasting attitude and a need to be noticed excessively within user, the using of new media give rise to psychology health problems that is Internet Addiction Disorder (IAD) and also make users be a less empathy and less sensitive toward their real society.Key Words : Representation, Semiotic, Barthes’ Semiotic, Don’t Hug Me I’m Scared 4.